The impact of tumor budding and single-cell invasion on survival in patients with stage III/IV locally advanced oral squamous cell carcinoma- results from a prospective cohort study - Hakim, Samer G.; Alsharif, Ubai; Falougy, Mohamed; Tharun, Lars; Rades, Dirk; Jensen, Justus (Frontiers in Oncology, 2024)
Tumor budding (TB) refers to small clusters of less than five tumor cells at the invasion front of a tumor. This study explicitly investigates the extreme variant of TB defined as single tumor cell invasion (SCI). Both TB and SCI are important histomorphologic risk factors postulated to indicate loss of cellular cohesion and aggressive invasion. In the present study, we investigated the survival outcomes in patients with TB and SCI in a single-center, prospectively maintained cohort and focused on locally advanced stage III/IV oral squamous cell carcinoma (OSCC). We included 129 patients with locally advanced OSCC (pT3 - pT4, pN0-pN+), correlated with cervical lymph node metastasis at the primary diagnosis by logistic regression, estimated the overall survival (OS) and cumulative events for oral cancer-specific survival (OCSS), local recurrence-free survival (LRFS), and locoregional recurrence-free survival (LRRFS) and the adjusted hazard ratios (HR) for TB and SCI using Cox’s proportional hazards regression models. TB was detected in 98 (76%) of the tumors, while SCI was observed in 66 (51%) patients. Patients with TB and especially SCI showed a clear trend toward local and locoregional recurrence. There was a significant association between TB and the occurrence of occult lymph node metastasis (OR=3.33 CI: 1.21-10.0, p=0.02). On multivariate analysis, TB had no detectable impact on survival outcomes. However, TCI was proved to be an independent risk factor for local recurrence (HR: 3.33, p=0.021). Involved and high-risk resection margins (R1, Rhr) as well as occult lymph node metastasis (N+), also impaired LRFS and OCSS (HR: 4.66, 4.93, 3.29; p=0.03, 0.01, and 0.002, respectively). This study demonstrates that TB and SCI in locally advanced OSCC function as an independent risk factor for local recurrences, as well as lymph node metastases. Both could serve as an additional parameter for stratifying therapy and escalating multimodal treatment approaches.